PENGARUH WEBSITE QUALITY DAN PERSEPSI RISIKO TERHADAP KEPERCAYAAN KONSUMEN DAN KEPUTUSAN PEMBELIAN ONLINE PADA GENERASI Z DI KOTA PEKANBARU - Meriska Christina; Restuti Sri; Nursanti Aida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The development of increasingly advanced technology has made the internet a medium that is not only used for communication, but also as a medium for shopping. Online shopping activities have become an activity that is commonly carried out by various groups, especially young people who are currently dominated by Generation Z. There are several things that play a role when consumers want to decide to purchase goods or services online. There are including the online shop’s website quality, the risk that consumers perceived as well as the trust that consumers have.This study aims to determine how much influence the things that can affect Consumer Trust and Online Purchasing Decisions on Generation Z in Pekanbaru City. Primary data were collected using a questionnaire as a research instrument. The study used 100 people classified as Generation Z in Pekanbaru City as respondents using the Non-Probability Sampling Technique. The method used is explanatory research with data analysis test, classical assumption test, hypothesis test and path analysis as a flow of data testing. Data testing is assisted by the SPSS version 25 application. The results of this study indicate that the Website Quality variable has a positive and significant effect on Consumer Trust and Online Purchasing Decisions. Perception of Risk has a negative and insignificant effect on Consumer Trust, but has a positive and significant effect on Online Purchasing Decisions. Consumer Trust has a positive and insignificant influence on Online Purchasing Decisions and there is no significant influence between Website Quality and Risk Perception on Online Purchasing Decisions through Consumer Trust.Keywords : Website Quality, Persepsi Risiko, Kepercayaan Konsumen, Keputusan Pembelian Online, Generasi Z